Peran Guru Pendidikan Agama Katolik dalam Mengatasi Kecanduan Gadget pada Siswa - Bukit, Friska Natalia; Sembiring, Mimpin (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – Gadget addiction is a condition where a person is said to be a gadget addict when they spend most of their time playing gadgets. Gadget addiction is a condition in which a person experiences excessive dependence on the use of electronic devices, such as cell phones or tablets, thus disrupting their daily life and health. The purpose of this study is to find out how the condition of gadget addiction in students and to find out the role of Catholic religious education teachers in overcoming gadget addiction in students.Method – The research method conducted by the author is Using qualitative methods, data was collected through observation, interviews, and documentation.The result of observations and interviews Data processing techniques through data reduction, data display, and conclusion drawing.Findings – The research findings show the high level of gadget addiction in students and in overcoming students' gadget addiction, teachers play five roles, namely as role models by giving examples of deactivating gadgets before learning, as learning managers by making lesson plans and using methods that are suitable for students, as motivators by motivating students such as giving positive praise and punishment, as facilitators by preparing books, and as facilitators by preparing books for students. Research Implications – The implication of this study shows that the high gadget addiction among SMA Negeri 1 Delitua students affects their academic productivity, mental health, and social interaction. PAK teachers act as role models, learning managers, motivators, facilitators, and mentors, which are effective in reducing gadget addiction in students.